Kekerasan dalam Pendidikan; Sejarah, Perkembangan dan Solusi - Halimatus Sa'diyah (Sekolah Tinggi Agama Islam YPBWI Surabaya, 2021)
Studies on the history of violence in education have not been widely discussed so far, especially in Indonesia, even though it is very important to study and find solutions so that violence does not occur again in education. The world of education is often associated with acts of violence considering the many cases of violence that have occurred so far, especially in Indonesia. Researchers try to study it to find a typology of violence in education and how to overcome the problem of violence that occurs in education. This paper is a type of library research through content analysis obtained from several references in the form of books and scientific articles. The result of this research is to formulate the concept of peace education (peace education) which can train students in reducing conflict in order to create peaceful conditions both intra-personally and interpersonally. Peace education - which is the substance of Islamic education - not only teaches students to think, but also stimulates students to think critically. This can be carried out using a holistic and participatory approach through the dialogue method so that learning is more meaningful.